Analisa Rute Transjateng Rute Purwokerto – Purbalingga Dengan Algoritma Dijkstra - Cindy Magnolia; Pungkas Subarkah; Reza Arief Firmanda; Dava Patria Utama (DoubleClick: Journal of Computer and Information Technology, 2021)
Transportation has grown very rapidly in the last few decades, including in Purwokerto, one of the cities in Central Java that is developing in its economic sector where transportation is one of the facilities needed for people who need high mobility to meet their needs, one of the transportation that is in demand is BRT, To reduce congestion and support the community's economy, the government launched the BRT Trans Jateng Bukateja - Purwokerto which has travel time savings so that fuel consumption is minimal and transportation costs can be optimized. In this study, the authors analyzed the BRT Trans Jateng Bukateja – Purwokerto route using the Djikstra method to measure efficiency and the fastest mileage by paying attention to vehicle specifications on the BRT Trans Jateng Bukateja – Purwokerto, the data used is the distance between shelters, passenger capacity, operating hours, bus departure distance and bus fuel consumption.